Glasovanje invalidov na volitvah in diskriminacija - Toplak, Jurij (Podjetje in delo, 2018)
Slovenia ratified the Convention on the Rights of Persons with Disabilities in 2008, but polling stations remained inaccessible. The state does not give disabled voters a possibility to vote independently and by secret ballot. In numerous cases, the Administrative Court and the Supreme Court found no violations. The Constitutional Court ruled that polling stations should be accessible, but the ruling has not yet been implemented in practice. Four years after the ruling, the authorities expect to hold the first election without discrimination. The article presents both rules and practices on accessibility of polling stations and voting. It also presents case law of the Administrative Court, Supreme Court, and Constitutional Court. The article critically assesses the constitutionality of the previous and new legislation in light of constitutional and international standards of elections, equality and prohibition of discrimination.
Keywords: diskriminacija; dostopnost; enakost; invalidi; volišča; volitve